IMPLEMENTING CIRC STRATEGY TO IMPROVE STUDENTS’ ABILITY IN READING COMPREHENSION AND WRITING EFL AT HIGHER EDUCATION LEVEL - Hartia Novianti; Rukminingsih Rukminingsih (STKIP PGRI Jombang, 2020)
This study was describe the improvement of students’ reading comprehension and writing ability through CIRC. In conducting this study, the reseracher collected data from students of second semester Speaking class in their second semester at STKIP PGRI Jombang. . The problems faced in this class are the students were still confused of how to find implicit and explicit information, word meaning, and reference word in reading comprehension, the students were still confused how to start producing narrative text and sometimes they lose their ideas in the middle of composing narative text because they were lack of vocabularies.The instruments used here were interview. observation, field note, questionnaires, and test. . Each cycle consisted of four meetings in which two meetings were for implementing reading comprehension and the other two meetings were for implementing writing. The results of the study show that CIRC can improve (1) students’ ability in reading compehension and writing and (2) teaching and learning process. Thus, CIRC can be an alternative teaching strategy that benefits for improving students’ achievement, ability, and participation in the teaching and learning process.